Pemanfaatan Limbah Minyak Jelantah dan Kulit Jeruk sebagai Lilin Aromaterapi dalam Rangka Menunjang Program Kewirausahaan di Lingkungan MGMP Kimia Jakarta Timur 2 - Pratiwi, Yussi; Dianhar, Hanhan; Amelia, Rizky; Nurhasanah, Nurhasanah; Fadillah, Muhammad (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: Many efforts are made to manage used cooking oil waste, namely by reusing it into a useful product such as aromatherapy candles by using the addition of fragrances such as essential oils contained in orange peels which can stabilize the nervous system, cause a relaxing effect, and as a mosquito repellent. The utilization of used cooking oil and orange peel is one of the efforts to minimize waste and make it an economically valuable product. The purpose of this activity is to utilize waste cooking oil and orange peels so that they become products that can be of economic value in the East Jakarta MGMP 2 environment. Method: Counseling and demonstrations held at PKP Jakarta Islamic School High School in August 2023. The data collection techniques were carried out by observation and questionnaire then the data was analyzed descriptively. Results: Chemistry teachers in the East Jakarta MGMP 2 environment are very enthusiastic and give a positive response to the activity of making aromatherapy candles from waste cooking oil and orange peels with the aim of minimizing environmental pollution so that the concept of simple waste treatment can be achieved. In addition, it can also create activities for the community so that it can help the community's economy through entrepreneurship. Conclusion: Waste cooking oil and orange peels can be utilized as aromatherapy candles to help the community's economy and improve environmental quality due to waste cooking oil that is not properly processed.